SURFER’S EAR – A HIDDEN CHALLENGE IN WATER SPORT: PATHOGENESIS, DIAGNOSIS AND TREATMENT STRATEGIES - Adam Skrobarczyk,; Agnieszka Dobrowolska,; Zuzanna Drewniak,; Marta Rząsa,; Karolina Rycman,; Martyna Sternik,; Kamil Wendrychowicz,; Filip Wróbel, (International Journal of Innovative Technologies in Social Science, 2025)
Background: External Auditory Canal Exostosis (EAE), or surfer’s ear, is a benign yet progressive condition involving new bone formation within the external auditory canal, typically triggered by repeated exposure to cold water and wind. This review summarises current knowledge on the anatomy, pathogenesis, clinical presentation, and management of EAE, including preventive and surgical strategies.Aim: The aim of this review is to evaluate the current understanding of the pathogenesis, clinical features, diagnostic methods, and therapeutic approaches to surfer’s ear, and to provide a comprehensive synthesis to support clinical practice and guide future research.Methodology: This literature review was conducted using PubMed, OVID and Google Scholar. Keywords included: “Surfer’s ear”, “Exostosis”, “Exostosis in aquatic athletes” and “Canaloplasty”. Studies were selected based on relevance and methodological quality.Results: EAE prevalence is high among water sports participants, particularly those exposed to cold water. Reported rates range from 38% to 75.1%, with the latter observed in German wind- and kitesurfers, a population relevant to Polish athletes due to comparable climatic conditions. Severity of exostoses strongly correlates with cumulative exposure to cold water and wind. Symptoms typically include water trapping, pain and hearing loss. Various instruments are used for surgical removal. Microdrills, though common, are associated with suboptimal postoperative outcomes and potential complications. Osteotomes present a safer alternative: a large retrospective study showed that osteotome-only excision resulted in the lowest rates of postoperative symptoms and complications, including tinnitus.Conclusion: EAE is a largely preventable condition driven by cumulative cold-water and wind exposure. Diagnosis is primarily clinical, with CT used for surgical planning. Consistent earplug use remains the most effective preventive measure. Increased awareness and preventive education in aquatic communities are needed. Future studies should refine risk assessment and evaluate newer surgical approaches.